A Comparative Analysis on the Different Food E-Commerce User Generated Content Affecting Millennials' Buying Intention - Manuel, Francesca; Andres, Danielle; Mamisay, Ella (International Journal of Social and Management Studies, 2022)
The paper aims to provide sufficient insights on the utilization of the different User-Generated Content on social media platforms created for businesses in the Food E-Commerce Industry, specifically on how it affects the buying intention of Millennial consumers. With this, the paper adopted a quantitative approach with a causal-comparative design. The researchers distributed an online survey questionnaire with close-ended and five-point Likert questions to 385 qualified respondents. The statistical tools, namely Chi-Square and Multiple Linear Regression, were applied to analyze the gathered data. The results strengthened the notion that the trend of social media is helping companies reach more consumers and promote what they offer to a larger audience with lesser expenses yet more value.